Wybrane cechy języka medycznego – terminologia, normalizacja, gatunki tekstów medycznych i relacje międzygatunkowe - Karwacka, Wioleta (Języki specjalistyczne w komunikacji interkulturowej, 2020)
This article discusses selected features of the medical language with special emphasis on Polish and English. The first discussed feature is medical terminology, in particular: Greek and Latin influences, eponyms and acronyms. The medical language is a controlled one, which is another aspect presented in this article. The next characteristic feature includes conventions related to particular medical genres. Finally, genre shift is briefly discussed.